2011
DOI: 10.1038/ejcn.2011.166
|View full text |Cite
|
Sign up to set email alerts
|

Beverage consumption among European adolescents in the HELENA study

Abstract: Background and Objective Our objective was to describe the fluid and energy consumption of beverages in a large sample of European adolescents Methods We used data from 2,741 European adolescents residing in 8 countries participating in the Healthy Lifestyle in Europe by Nutrition in Adolescence Cross Sectional Study (HELENA-CSS). We averaged two 24-hour recalls, collected using the HELENA-dietary assessment tool. By gender and age subgroup (12.5–14.9 y and 15–17.5 y), we examined per capita and per consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
3
15

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 41 publications
12
91
3
15
Order By: Relevance
“…However, it is important to highlight that our observations are consistent with studies performed in other countries, which reported elevated consumption of sugar-rich food products among adolescents, specifically soft drinks, candies, and desserts 2,4,6,9,22 .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…However, it is important to highlight that our observations are consistent with studies performed in other countries, which reported elevated consumption of sugar-rich food products among adolescents, specifically soft drinks, candies, and desserts 2,4,6,9,22 .…”
Section: Discussionsupporting
confidence: 74%
“…It is noteworthy that many studies evaluate only the consumption of soft drinks individually, not together with the ingestion of sweets, hindering the analysis of accumulated consumption of sugar-rich food products and its associated factors 5,6,18,20,22 .…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The Healthy Lifestyle in Europe by Nutrition in Adolescence Cross Sectional Study (HELENA-CSS), which evaluates the amounts of beverages consumed among adolescents aged 12.5-17.5 across urban areas from 10 European cities, showed that sugar-sweetened beverages were the second most consumed beverages (430 ml per day) aer water, which is the largest contributor to uid consumption (821 ml per day) in adolescents. 7 Although uid intake is not closely associated with hydration status, it is commonly used as an approximate measure of hydration because it is easy to measure. 8 Recent statements on water requirements have been based on retrospective recalls of water intake from food and beverages among healthy populations.…”
Section: Consumption Of Soft Drinksmentioning
confidence: 99%